Searching The New Culprit of Optic Neuritis: The Role of Vitamin D: Poster Presentation - Case Report - Ophthalmologist - ANAK AGUNG MAS PUTRAWATI TRININGRAT; Made Paramita Wijayati; Putu Ayu Wulansari (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Low vitamin D status has long been associated in multiple sclerosis patient with higher risk of disease progression and frequent relapses. Vitamin D plays an important role in modulating the immune process responsible for demyelination. To this date, the study on vitamin D deficiency in optic neuritis case is still rare. Case Illustration : Female, 20 years old, presenting with bilateral sudden visual loss since 1 week prior. The patient looked relatively pale and complained of accompanying headache and myalgia. Visual acuity in both eyes were light perception with dilated pupils and posterior segment showing optic disc swelling. CBC, infection and autoimmune screening came within normal limit and brain MRI further confirmed the presence of optic neuritis. The patient was given high dose intravenous steroid but showed no improvement. Later, she was screened for nutrient deficiency and found sign of low serum 25-hydroxyvitamin D. After one week of oral supplementation and neuroprotective agents, her vision drastically improved to 6/6 in both eyes. Discussion : Vitamin D deficiency nowadays is getting more prevalent in high risk individuals with low dietary intake and sunlight exposure. Recent study found that mean serum vitamin D level were significantly lower in autoimmune optic neuritis (ON) and were associated with ON attack severity. Vitamin D sufficiency is associated with better inflammatory outcome and long term neurodegenerative measures in demyelinating diseases, as shown by improvement in RNFL thickness after attack. Conclusion : Screening for vitamin D deficiency is essential to consider in managing patient with atypical optic neuritis.